Outcomes of social media marketing in sport brands - Dias, Á.; Pereira, L.; Lopes da Costa, R. (International Journal of Service Science, Management, Engineering, and Technology, 2022)
In an increasingly globalized world, social networks appear as an indispensable tool for sports clubs, as they make it easier for them to reach a large number of supporters. The main objective of this study is to measure the impact that this commitment between supporter and club has on the social networks, on the purchase and reference intention. Based on two sequential studies (one survey and in-depth interviews), the methodology aimed to help understand both the viewpoint of the fans and decision-makers. The results show that the commitment between the supporter and the club on the social networks has a positive influence on the relationship between the two; the commitment between the supporter and the club on the social networks has a positive influence on the intention of fans to buy; the commitment between the supporter and the club on the social networks has a positive influence on the intention of reference by the fans